ASSESSING LITHIUM LEVELS AFTER ONCE DAILY DOSAGE IN PATIENTS OF BIPOLAR AFFECTIVE DISORDER IN A CLINICAL SETUP - Khan, Sikandar Ali; Bajwa, Asif Azeem; Akhtar, Farrukh (Pakistan Armed Forces Medical Journal, 2019)
Objective: To determine the variations in serum lithium levels in 24 hrs and to establish the time required for lithium to reach its peak levels after once daily dosage. Study Design: Case series study. Place and Duration of Study: This study was carried out at a tertiary care hospital, from Dec 2016 to Jun 2017. Patients and Methods: One hundred patients of Bipolar Affective Disorder who were receiving lithium for treatment or prophylaxis were selected randomly from OPD (with negative history of renal co-morbidity and intake of diuretics). These selected patients were admitted in hospital for five days with their consent. These admitted patients were given 800mg of lithium under supervision ensuring adherence to single dose lithium ingestion for five days. During their admission a brief history regarding their illness was taken meanwhile patients were screened for any possible renal co-morbidity. After 5 days of monitored lithium ingestion serial serum samples of the patients in the study were collected with their consent. Samples were collected after 0, 2, 4, 6, 12, 18 hours of ingestion of a single dose (800mg) of slow release lithium carbonate. Results: Serum lithium levels in 77% (n=68) of samples taken at 0hrs ranged from 0.2-0.5meq/ltr, in 61.7% (n=50) of second sample taken at 2hrs ranged from 0.3-0.6meq/ltr, after 4hrs 74.3% (n=61) of samples serum lithium ranged 0.5-1.0meq/ltr, indicating further increase in serum lithium levels. Six hours after the ingestion of lithium 85% (n=70) of samples revealed increased serum lithium level to the range of 0.5-0.9meq/ltr. Twelve hours after the ingestion of lithium 77.7% (n=70) had serum lithium level 0.4-0.7meq/ltr indicating that now levels had started to fall. After 18 hours in 80.2% (n=70) samples lithium levels were 0.3-0.6meq/ltr showing downward slope which was still higher than baseline. Conclusion: Appropriate lithium level can only be obtained when serum sample is taken at appropriate time. Appropriate time of sample collection for serum lithium level is twenty four hours after the last dose of lithium if slow release preparation is being used.